Real-life experience with inotersen at CEPARM, Hospital Universitário Clementino Fraga Filho, Universidade Federal do Rio de Janeiro - Dias, Moises; Pinto, Luiz Felipe; Pinto, Marcus Vinícius; Gervais, Renata; Accioli, Paula; Amorim, Gabriela; Guedes, Mariana; Gomes, Carlos Perez; Pedrosa, Roberto Coury; Waddington-Cruz, Márcia (Arquivos de Neuro-Psiquiatria, 2024)
Background Hereditary transthyretin amyloidosis (ATTRv) is an inherited, progressive, and fatal disease still largely underdiagnosed. Mutations in the transthyretin (TTR) gene cause the TTR protein to destabilize, misfold, aggregate, and deposit in body tissues, which makes ATTRv a disease with heterogeneous clinical phenotype.Objective To describe the long-term efficacy and safety of inotersen therapy in patients with ATTRv peripheral neuropathy (ATTRv-PN).Methods Patients who completed the NEURO-TTR pivotal study and the NEURO-TTR OLE open-label extension study migrated to the present study and were followed-up for at least 18 more months to an average of 67 months and up to 76 months since day 1 of the inotersen therapy (D1–first dose of inotersen). Disease progression was evaluated by standard measures.Results Ten ATTRv-PN patients with Val30Met mutation were included. The mean disease duration on D1 was of 3 years, and the mean age of the patients was of 46.8 years. During an additional 18-month follow up, neurological function, based on the Neuropathy Impairment Score and the Polyneuropathy Disability Score, functionality aspects (Karnofsky Performance Status), and nutritional and cardiac aspects were maintained. No new safety signs have been noted.Conclusion The treatment with inotersen was effective and well tolerated for the average of 67 months and up to 76 months. Our results are consistent with those of larger phase-III trials.
Keywords: Amyloidosis; Peripheral Nervous System Diseases; Amyloid Neuropathies, Familial; Mutation, Missense; Amyloidosis, Hereditary, Transthyretin-Related; Inotersen